The Use of Geometric Transformation Board (TRANSMET) Teaching Aids to Increase Students’ Interest in Learning Reflection Material - Muhammad Sofyan Apriyono; Yesi Puspitasari; Tri Astindari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2026)
This study aims to describe the use of the geometry transformation board (TRANSMET) teaching aid to increase students' interest in reflection materials. This research employed a descriptive qualitative approach involving students who participated in geometry transformation learning. The researchers collected data through observation, interviews, and documentation. They analyzed the data using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing/verification. The findings indicate that the use of the TRANSMET teaching aid increases students' learning interest, as shown by improved activeness, attention, and enthusiasm during the learning process. Furthermore, the teaching aid helps students understand reflection concepts more easily by allowing them to observe the reflection of geometric figures directly. Therefore, the TRANSMET teaching aid is effective as a learning medium for enhancing students' interest in geometry transformation reflection materials.